Electronic properties of van der Waals heterostructures based on F-GaN-H stacking and TMDs single layer. (December 2022) - Li, Enling; Wang, Fangping; Cui, Zhen; Ma, Deming; Shen, Yang; Shen, Pengfei; Zhao, Hongyuan; Tang, Yuanhe
Abstract: The self-doping effects in atomic layer semiconductor materials have shown great potential for the 2D electronics and optoelectronics devices. In this paper, using the density functional theory (DFT), nonvolatile self-doped p-n junctions are formed in GaN based heterostructures which based on the stacking of the hydro-fluorination buckled GaN monolayer (ML) and bilayer (BL) and transition metal dichalcogenides (TMDs) single layer. The electronic properties demonstrated that the space distribution of carrier, and the band structures of the heterostructures depend on the polarization of GaN. The anisotropic hole and electron carrier concentration ( c h and c e ) are obtained in the WS2 (MoS2 )/ML, BL/WSe2, and WS2 (MoS2 )/BL heterostructure systems respectively. Moreover, the nonvolatile self-doped p-n junctions are achieved in type-III TMDs/ML (BL) and (BL) ML/TMDs heterostructures with the ultrahigh hole and electron carrier concentration. The type of band structures and carrier of the TMDs/ML (BL) and (BL) ML/TMDs heterostructure systems have been modulated by the self-doped induced by the polarization of GaN, which provides a new doping strategy for 2D GaN based (or polar) materials and simplifies the device fabrication in electronic and optoelectronic field. Highlights: The stability of the heterostructure systems have been systematically studied. The spatial distribution of carrier and the type of band structures in these heterostructures can be controlled by the polarization reversal of the GaN. The anisotropic carrier concentration are obtained in the WS2 (MoS2 )/ML, BL/WSe2, and WS2 (MoS2 )/BL respectively. The self-doped p-n junctions are formed in TMDs/ML (BL) and (BL) ML/TMDs and with ultrahigh carrier concentration.